Sjukvårdsbehov till sjöss - En jämförelse gällande sjukvårdsutbildningens återspegling utav verklighetens beskrivna behov av sjukvård till sjöss - Eliasson, Adam; Thunander, Axel (My University, 2013)
As second officer in the merchant fleet, it is common to act as the medical caregiver on board. When taking into account that medical care is only a supporting role for the 2nd officer, it becomes clear that the need for an accurate and optimal education is of a high necessity. A theoretical assumption has been made in the purpose of strengthen the medical safety on board. The hypothesis is based on investigating regarding the fact that invigorating the caregivers’ Educational Efficiency, would result in a better treatment, all according to Utstein Chain of Survival. By preparing the students for reality’s scenarios, the Educational Efficiency may be improved. The purpose of the study was to investigate if reality’s need of medical treatment is reflected in the education given at the Master Mariner-programme at Chalmers University of Technology, Gothenburg Sweden. Reported medical cases from Radio Medical, Sweden, have been compared to learning objectives from the education. The different cases are based upon reported calls from the years; 1997, 2002 and 2007. These numbers are paralleled with the education year 2013. The method, being used is based upon descriptive statistics divided by nominal scale. In the comparison between given education and reality, the different groups were labeled by ICPC-2. A percentage distribution has then been made to investigate if the education corresponds to reality. The result shows that there is a distinctly missed focus in some categories. The correlation between education and reality is only consistent in three of eleven groups. Remaining parts are either under- or overrepresented. The conclusion points to the fact that due to lack of other pertinent science it becomes complicated to create a reality-based education. There is also a problem regarding internationally written regulations, which the education is based on.
Keywords: Hälsovetenskaper; Utbildningsvetenskap; Health Sciences; Educational Sciences